2017
DOI: 10.18203/2320-6012.ijrms20171820
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of serum cortisol levels and its correlation with salivary cortisol levels in coronary artery disease patients with and without periodontitis: a cross sectional study

Abstract: Background: Atherosclerosis refers to combination of changes in the intima of arteries, consisting of focal accumulation of lipids, complex carbohydrates, blood and blood products, fibrous tissue, calcium deposits and associated medical changes. Ischemic heart disease (IHD) refers to a group of closely related syndromes that is caused by an imbalance between myocardial oxygen demand and blood supply.Methods: A cross-sectional study was conducted on 63 patients, aged 30-65 years, with known coronary artery dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
(28 reference statements)
2
3
2
Order By: Relevance
“…The salivary cortisol levels were higher as compared to serum cortisol in our study. This is in contrast with the findings in one of the previous studies of George et al 30 where they found higher cortisol serum values as compared to salivary values, which may be attributed to the differential methodology of processing the samples. The findings of our study revealed that saliva exhibits a more efficient and accurate profile of the local changes occurring in the periodontal environment as compared to serum.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The salivary cortisol levels were higher as compared to serum cortisol in our study. This is in contrast with the findings in one of the previous studies of George et al 30 where they found higher cortisol serum values as compared to salivary values, which may be attributed to the differential methodology of processing the samples. The findings of our study revealed that saliva exhibits a more efficient and accurate profile of the local changes occurring in the periodontal environment as compared to serum.…”
Section: Discussioncontrasting
confidence: 99%
“…The salivary cortisol levels were higher as compared to serum cortisol in our study. This is in contrast with the findings in one of the previous studies of George et al . where they found higher cortisol serum values as compared to salivary values, which may be attributed to the differential methodology of processing the samples.…”
Section: Discussioncontrasting
confidence: 99%
“…However, salivary cortisol levels in Group II when compared with the salivary cortisol levels in the control group showed a nonsignificant P value of .154. The results were similar to the study conducted by George et al [23] They assessed salivary cortisol response to psychological depression and its relationship to psychological variables. They subjected a modified version of the Trier Social Stress Test to all patients, which lasted for 20 minutes.…”
Section: Discussionsupporting
confidence: 89%
“…The serum and salivary cortisol levels were significantly increased in an ascending order from Group I to Group III indicating cortisol levels are correlated to the severity of periodontal disease. It is suggested that the salivary cortisol levels are increased in smokers which has a definite but short‐term deleterious effect on the neuroendocrine system and thus manifests in a greater severity of destruction as is seen in the present study 32,33 . The salivary cortisol levels obtained in our study were greater than the serum cortisol levels which may be ascribed to the effective and accurate profile of local changes being reflected in salivary environment than the serum.…”
Section: Discussionsupporting
confidence: 51%
“…It is suggested that the salivary cortisol levels are increased in smokers which has a definite but short-term deleterious effect on the neuroendocrine system and thus manifests in a greater severity of destruction as is seen in the present study. 32,33 The salivary cortisol levels obtained in our study were greater than the serum cortisol levels which may be ascribed to the effective and accurate profile of local changes being reflected in salivary environment than the serum. There are conflicting reports pertaining to the elevated levels of cortisol in serum and saliva with Gossain et al, 34 and Kirschbaum et al, 35 reporting non elevated values.…”
Section: Discussionmentioning
confidence: 57%